Preliminary Evaluations of FGOALS-g2 for Decadal Predictions - 王斌 刘咪咪 俞永强 李立娟 林鹏飞 董理 刘利 刘骥平 黄文誉 徐世明 申思 普业 薛巍 夏坤 王勇 孙文奇 胡宁 黄小猛 刘海龙 郑伟鹏 吴波 周天军 杨广文 (Advances in atmospheric sciences, 2013)
The Flexible Global Ocean-Atmosphere-Land System model, Grid-point Version 2 （FGOALS-g2） for decadal predictions, is evaluated preliminarily, based on sets of ensemble 10-year hindcasts that it has produced. The results show that the hindcasts were more accurate in decadal variability of SST and surface air temperature （SAT）, particularly in that of Nifio3.4 SST and China regional SAT, than the second sample of the historical runs for 20th-century climate （the control） by the same model. Both the control and the hindcasts represented the global warming well using the same external forcings, but the control overestimated the warming. The hindcasts produced the warming closer to the observations. Performance of FGOALS-g2 in hindcasts benefits from more realistic initial conditions provided by the initialization run and a smaller model bias resulting from the use of a dynamic bias correction scheme newly developed in this study. The initialization consists of a 61-year nudging-based assimilation cycle, which follows on the control run on 01 January 1945 with the incorporation of observation data of upper-ocean temperature and salinity at each integration step in the ocean component model, the LASG IAP Climate System Ocean Model, Version 2 （LICOM2）. The dynamic bias correction is implemented at each step of LICOM2 during the hindcasts to reduce the systematic biases existing in upper-ocean temperature and salinity by incorporating multi-year monthly mean increments produced in the assimilation cycle. The effectiveness of the assimilation cycle and the role of the correction scheme were assessed prior to the hindcasts.